Awareness, Utilization, and Preferences of Harm Reduction Interventions among Street-Involved Young Adults in Boston. (16th April 2022) - Noyes, Elizabeth A.; Dunleavy, Spencer; Mail, Victoria; Plakas, Isabel; Keyes, Susan; Gaeta, Jessie M.; Obando, Aura; Paci, Elizabeth; Lent, Claudia; Regis, Craig; Taveras, Elsie M.; Yule, Amy M.; et al.
Abstract: Objectives: This study explores knowledge and utilization of, barriers to, and preferences for harm reduction services among street-involved young adults (YA) in Boston, Massachusetts. Methods: This cross-sectional survey of YA encountered between November and December 2019 by a longstanding outreach program for street-involved YA. We report descriptive statistics on participant-reported substance use, knowledge and utilization of harm reduction strategies, barriers to harm reduction services and treatment, and preferences for harm reduction service delivery. Results: The 52 YA surveyed were on average 21.4 years old; 63.5% were male, and 44.2% were Black. Participants reported high past-week marijuana (80.8%) and alcohol (51.9%) use, and 15.4% endorsed opioid use and using needles to inject drugs in the past six months. Fifteen (28.8%) YA had heard of "harm reduction", and 17.3% reported participating in harm reduction services. The most common barriers to substance use disorder treatment were waitlists and cost. Participants suggested that harm reduction programs offer peer support (59.6%) and provide a variety of services including pre-exposure prophylaxis (42.3%) and sexually transmitted infection testing (61.5%) at flexible times and in different languages, including Spanish (61.5%) and Portuguese (17.3%). Conclusions: There is need for comprehensive, YA-oriented harm reduction outreach geared toward marginalized YA and developed with YA input to reduce barriers, address gaps in awareness and knowledge of harm reduction, and make programs more relevant and inviting to YA.